2020
DOI: 10.1038/s10038-020-0741-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic variability of PAX2-related disorder in the Japanese population

Abstract: Pathogenic variants of paired box gene 2 (PAX2) cause autosomal dominant PAX2related disorder, which includes renal coloboma syndrome (RCS). Patients with PAX2related disorder present with renal and ophthalmological pathologies, as well as with other abnormalities, including developmental problems and hearing loss. We sequenced PAX2 in 457 patients with congenital anomalies of the kidney and urinary tract or with renal dysfunction of unknown cause and identified 19 different pathogenic variants in 38 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…A frameshift deletion of PAX2 in a family with optic nerve colobomas, renal hypoplasia and VUR (Sanyanusin et al, 1995) represents the first reported single gene defect causation of congenital anomalies of the kidney and urinary tract (CAKUT). Subsequently, larger patient cohort studies confirmed PAX2 mutations as an important cause of syndromic CAKUT and the establishment of RCS as a separate disease entity (Madariaga et al, 2013; Rossanti et al, 2020; Thomas et al, 2011; Weber et al, 2006). PAX2 is a member of the paired box (PAX) family of transcriptional regulatory genes with nine members described in humans.…”
Section: Discussionmentioning
confidence: 97%
“…A frameshift deletion of PAX2 in a family with optic nerve colobomas, renal hypoplasia and VUR (Sanyanusin et al, 1995) represents the first reported single gene defect causation of congenital anomalies of the kidney and urinary tract (CAKUT). Subsequently, larger patient cohort studies confirmed PAX2 mutations as an important cause of syndromic CAKUT and the establishment of RCS as a separate disease entity (Madariaga et al, 2013; Rossanti et al, 2020; Thomas et al, 2011; Weber et al, 2006). PAX2 is a member of the paired box (PAX) family of transcriptional regulatory genes with nine members described in humans.…”
Section: Discussionmentioning
confidence: 97%
“…A wide variety of clinical phenotypes have been reported in individuals with PAX2- related disorder [ 8 , 9 , 11 ]. Dysplasia of the optic nerve was the main ophthalmological finding of the disorder, which covered 63% of literature-based cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is important for cell lineage specification in multicellular organisms [ 19 ]. A broad variety of non-renal and non-ophthalmological manifestations have been recorded in individuals with PAX2 -related disorders [ 3 , 11 , 20 ]. We should pay more attention to clinical assessment and tracking of multiple system development in the patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial role of the Pax2 genes in brain development and function have become apparent in recent reports on Pax2 -related diseases in a Japanese population describing that the patients with Pax2 mutations exhibit developmental abnormalities, including autism spectrum disorders (ASDs), language delay, or mental retardation. 7 , 8 Emerging evidence demonstrates that PAX2 proteins execute important functions during central nervous system development and in adult neurogenesis. 9–15 However, the molecular mechanisms required to establish and maintain these functional connections are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%